Health risk assessment on heavy metals in urban street dust of Tianjin based on trapezoidal fuzzy numbers. Issue 3 (2nd April 2016) - Hu, Beibei; Liu, Baiqiao; Zhou, Jun; Guo, Jinting; Sun, Zongbin; Meng, Weiqing; Guo, Xin; Duan, Jiahao
ABSTRACT: The aims of this article were to investigate heavy metals concentrations in urban street dust of Tianjin, to examine spatial variations of heavy metals pollution, and to assess their health risk to local populations. Urban street dust samples were collected from 144 typical crossroads in an urban area of Tianjin. Levels of heavy metals were determined by atomic absorption spectrophotometer analyzer. Given comprehensive consideration of the complexity and uncertainty of health risk assessment, trapezoidal fuzzy number was introduced to assess the health risk of heavy metals in the urban street dust of Tianjin. The results showed that the pollution of heavy metals in the urban street dust of Tianjin was serious. The relatively serious metal pollution tended to be located in the center, north, northeast, and southeast of the study area. The research indicated that heavy metals in street dust had caused non-cancer hazard to children but had not caused non-cancer or cancer hazard to adults. The direct ingestion of dust via hand-mouth contact behaviors was the major exposure pathway for health risk.